Penerapan Prinsip Akuntabilitas dan Transparansi dalam Perencanaan Anggaran Pendapatan dan Belanja Desa : Pada Desa Tanggul Wetan Kabupaten Jember - Mufida Ulima Wardani; Oryza Ardhiarisca (Politeknik Negeri Jember, 2022)
This study aims to explain the application of the principles of accountability and transparency in planning financial management through the preparation of the village income and expenditure budget (APBDes) in the village of Tanggul Wetan. This principle is based on the indicators in the Minister of Home Affairs Regulation number 114 of 2014 and the Minister of Home Affairs Regulation number 20 of 2018. The research can be categorized as qualitative research with primary data sources and secondary data. The data was collected through interviews and documentation. Data analysis techniques use the Miles and Huberman models. To ensure the validity of the data, a triangulation technique was used, namely source triangulation. The results of this study indicate that Tanggul Wetan Village has implemented the principles of transparency and accountability in planning the APBDes.